China-Africa economic partnership: a win-win game? - Abuhatab, Assem (Ciência & Trópico, 2013)
ABSTRACT The dramatic new trend in South-South economic relations is transforming traditional patterns of economic development, and this is nowhere more evident than in China-Africa economic cooperation CAEC. As indicated by several researchers, these new South-South economic relations present real opportunities, as well as challenges to African countries. As regard to CEAC, while the expansion of trade and investment between Africa and China has been generally welcomed, concerns have been expressed about how China’s growing presence might affect African development. But what roles exactly has China played? What drives China’s trade and financial involvement in Africa? What are the implications of the relationship for other development partners of Africa? This proposal aims to shed light on the ongoing debate on CEAC and develop a framework for the analysis of the socio-economic impacts of CEAC on African countries. KEYWORDS: China. Africa. CEAC.Financial involvement. Parceria econômica China-África: um jogo vantajoso a todos? RESUMO A nova e dramática tendência nas relações econômicas Sul-Sul está transformando os padrões tradicionais de desenvolvimento econômico, e isso é mais evidente do que na China-África de Cooperação Econômica, CAEC. Como indicado por diversos pesquisadores, essas novas relações econômicas Sul-Sul apresentam oportunidades reais, assim como os desafios para os países africanos. No que diz respeito ao CEAC, enquanto a expansão do comércio e do investimento entre a África e a China tem sido geralmente bem-vinda, as preocupações foram expressas sobre como a crescente presença da China pode afetar o desenvolvimento africano. Mas quais papéis a China realmente teve? O que impulsiona o comércio da China e seu envolvimento financeiro na África? Quais são as implicações da relação para outros parceiros de desenvolvimento na África? Esta proposta tem como objetivo lançar luz sobre o debate em curso sobre a CEAC e desenvolver um quadro para a análise dos impactos socioeconômicos da CEAC nos países africanos. PALAVRAS-CHAVE: China. Países africanos. Relações econômicas. CAEC.